Efeito temporal sobre caracteristicas morfoagronomicas de genótipos de girassol no cerrado do Distrito Federal em safrinha de 2015 e 2016. - BRIGE, F. A. A. (2017)
Título em inglês: Temporal effect on morphoagronomic characteristics of genotypes of sunflower in the brazilian savannah at Distrito Federal in the second crop of 2015 and 2016.